Analisis kesalahan ejaan bahasa jawa pada karangan narasi peserta didik kelas v sekolah dasar - Medy Hanida; Joko Daryanto; Hadiyah Hadiyah (Didaktika Dwija Indria, 2023)
Javanese language becomes important to be learned by students due to the lack of preservation of the use of Javanese language. Javanese language lessons are needed which can also preserve Indonesian culture. There are still found spelling errors in the Javanese spelling among the students. So, this study is about examine the errors of Javanese Language rules in fifth grade elementary student’s narrative essay. The aims of the study is for analyzing Javanese misspellings and the causes of these errors. This study is a qualitative research which describes the data detailed. This research data is taken from document studies of narrative text, interviews with teachers and learning observations. Data validity check used in this research are theoretical triangulation and source triangulation. This research was conducted with 12 data samples from students' narrative essays. Spelling errors that were found included errors in the use of letters, writing words, using punctuation marks and language interference. There are three dominant factors that cause language errors that occur in students, the influence of other languages that are more mastered than Javanese, lack of understanding of Javanese, lack of lessons that discuss in detail about the rules of Javanese writing.